Geological and Geochemical Studies of the Gold-Bearing Quartz-Fuchsite Vein at the Dome Mine, Timmins Area - Moritz, Peter Robert (My University, 1988)
The Quartz-Fuchsite vein at the Dome Mine, Timmins area, has been the subject of an integrated field, petrographic, geochemical, and fluid inclusion study to characterize the site and the cause of ore deposition, and to establish the source of ore components in Archean lode gold deposits.
The vein lies in a zone of carbonatized komatiites at the contact with a unit of slates. The wall rock alteration that accompanied ore genesis is centered around a porphyry lens located in the zone of carbonatized rocks. The location of the Quartz-Fuchsite vein is coincident with the outer rim of the alteration envelop.
A high pore fluid regime that developed in the carbonatized komatiites in proximity to the slates resulted in hydraulic fracturing and genesis of the Quartz-Fuchsite vein. Massive and barren quartz was deposited during protracted stages of fracture growth, while banded and gold-bearing quartz was formed during repetitive and brief periods of crack-seal vein growth. Quartz veining took place before the compressional deformation which has affected the Timmins area.
Fluid inclusion studies indicate that the hydrothermal fluid contemporaneous with quartz veining and gold deposition was a low salinity CH₄-rich H₂O-CO₂ fluid that underwent intermittent unmixing. Phase separation was promoted during pressure drops in fractures that accompany the crack-seal vein growth mechanism. The strong partitioning of CO₂ and CH₄ into the vapor during unmixing resulted in a shift in the remaining fluid toward higher pH and fO₂. As a consequence, gold complexes were probably destabilized in the hydrothermal fluid and deposited with quartz in crack-seal veins.
Lead isotope studies of whole rocks and galenas associated with gold in the Quartz-Fuchsite vein suggest a genetic link between the gold mineralization and the quartz-feldspar porphyries of the Dome Mine environment, although other source reservoirs cannot be ruled out on the basis of lead isotopes alone. Sulfur isotope compositions of pyrites and galenas from the Quartz-Fuchsite vein are compatible with a magmatic or a metamorphic fluid.
The weight of evidence indicates that the development of the gold mineralization in the Quartz-Fuchsite vein is genetically related to the emplacement of quartz-feldspar porphyries in the Dome Mine environment. The ultimate source of gold and the mineralizing fluid is probably a deeper seated magma, or possibly the lower crust.
Keywords: Geology; Geology